The development of design competence of students in the graphic preparation (Pedagogy of Higher and Secondary Education, 2013)
Tsvirkun L. O. The development of design competence of students in the graphic preparation.The article deals with the scientific concept of «graphic literacy», «graphic competence», «graphics professional competence», «design and engineering expertise», clarifies the nature of the concepts in the image of students, specifies the terms and focuses on the importance of the development of design competence of students in the study of graphic disciplines.
Keywords: graphic literacy; graphical competence; graphics professional competence; design and engineering expertise